Identification, characteristics and seasonal evolution of surface thermal fronts in the Argentinean Continental Shelf - Rivas, Andres Lujan (2010)
The location and seasonal variability of surface thermal fronts along the Argentinean Continental Shelf (38-55°S) were studied using 18 years (1985-2002) of sea surface temperature (SST) satellite data. Monthly SST gradients were calculated and a threshold was used to identify frontal pixels. Frontal areas were classified into 4 zones according to their seasonal evolution and the main forcings leading to the front's formation were identified for each group. The shelf break front was easily detected due to the large number of frontal pixels in the region and its high mean gradient values. This front showed a marked annual cycle and relatively constant position associated to the bottom slope; it tended to be located where the core of the Malvinas current is closest to the shelf. Tidal fronts also showed a strong annual cycle, being detected in three well-defined regions during spring and summer. Along the coasts of Tierra del Fuego and Santa Cruz, the combination of strong tidal mixing and low-salinity coastal plumes led to semi-annual seasonal cycles of frontal intensity and persistence that showed a relative maximum in winter. A similar behavior (semi-annual) was found at the coast off the Buenos Aires Province. There, the coastal dilution and the bathymetric gradient generated near-coastal fronts that changed direction seasonally. In the northern mid-shelf, a front linked to the intrusion of warm waters formed in the San Matías Gulf was identified during the winter.